Predicting Physics Students’ Academic Performance: The Impact of Attitude, Self-Efficacy, and Personality Traits - Eric Appiah-Twumasi (Journal of Research in Education and Pedagogy, 2024)
The study examined the predictive impact of attitude, self-efficacy, and personality traits on the academic performance of high school students in physics. A multistage random sampling technique was used to select 210 research subjects between the ages of 16 and 22 (SD=1.80) from three high schools in the Berekum East Municipality of Ghana. Three standardised questionnaires as primary data sources, namely: Attitude Toward Physics Learning (ATPL), Physics Learning Self-Efficacy (PLSE), and Students’ Personality Trait Inventory (SPTI), and additionally, Students’ Physics Mock Examinations scores as a secondary data source, were used for data collection and analysis through multiple regression. Data collected from respondents were compiled, sorted, edited and coded into the Statistical Package for the Social Sciences (SPSS) version 23. The results revealed a joint impact of 21.100% of the variance in attitude, self-efficacy, and personality traits in predicting the academic performance of students in physics. Furthermore, the multiple regression analysis revealed that student attitudes, self-efficacy, and personality traits significantly impact student academic performance in physics. The analysis further revealed that students’ personality traits best explained students’ academic performance in Physics (β = 0.232, t = 3.423; p < 0.050), followed by self-efficacy (β = 0.192, t = 2.738; p < 0.050), and attitude (β = 0.121, t = 2.011; p < 0.05). Based on the results obtained, the study recommended that physics students in the Berekum East Municipality’s attitudes, self-efficacy, and personality traits should be given greater attention by physics teachers, and other stakeholders because of their positive impact on students’ academic performance in physics.